2015
DOI: 10.1513/annalsats.201507-473oc
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Outcome of Diffuse Acute Infectious Bronchiolitis in Adults

Abstract: The three most common etiologies of DAIB in the studied adults were M. pneumoniae, influenza virus, and H. influenzae. None of the patients with DAIB developed postinfectious bronchiolitis obliterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
10
1
2
Order By: Relevance
“…28 In a previous study, the rate of diffuse bronchiolitis was reported to be 1.2% among community-acquired lower respiratory tract infections. 19 The difference between this rate and the value found in the present study for the bronchiolitis pattern is explained by the different definitions used. In the present study, bronchiolitis was defined as either the presence of centrilobular nodules or a tree-in-bud pattern in most lesions with or without GGO or consolidation in the present study, whereas, in the previous study, diffuse acute infectious bronchiolitis was defined as multiple centrilobular nodules in 4 or more lobes.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…28 In a previous study, the rate of diffuse bronchiolitis was reported to be 1.2% among community-acquired lower respiratory tract infections. 19 The difference between this rate and the value found in the present study for the bronchiolitis pattern is explained by the different definitions used. In the present study, bronchiolitis was defined as either the presence of centrilobular nodules or a tree-in-bud pattern in most lesions with or without GGO or consolidation in the present study, whereas, in the previous study, diffuse acute infectious bronchiolitis was defined as multiple centrilobular nodules in 4 or more lobes.…”
Section: Discussioncontrasting
confidence: 82%
“…28 In the present study, more than 40% of cases in the bronchiolitis group were caused by M. pneumoniae, which concurs with the findings of a previous study, in which M. pneumoniae was determined to be the most common pathogen of diffuse acute infectious bronchiolitis in adults. 19 Interestingly, common CAP pathogens, such as C. pneumoniae, S. pneumoniae and K. pneumoniae, also cause a bronchiolitis pattern. The mechanisms responsible for centrilobular nodules or tree-in-bud pattern in some patients and consolidation or GGO in others can be explained by the up-or down-regulations of host cell-mediated immunity, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations